Delayed Facial Nerve Paralysis After Tympanomastoidectomy. Incidence, Aetiology and Prognosis - MUHAMMAD RIAZ, SAMI MUMTAZ, MIRZA M SARWAR, TAHIR RASHID (Journal of Fatima Jinnah Medical University, 2018)
Background: Facial nerve paralysis is a well known complication of tympanomastoid surgery. In certain cases facial nerve is paralyzed without any injury a few days after surgery, known as Delayed Facial Nerve (DFN) palsy. It can occur two weeks after surgery. A retrospective study was conducted at ENT Unit –II, Fatima Jinnah Medical College / Sir Ganga Ram Hospital ( FJMC/SGRH), Lahore, to document frequency of, etiological factors and long term prognosis. Material and Methods: The study period spanned over six years (May 2008 – May 2014) during which a total of 350 patients underwent tympanomastoid surgery. Three patients (0.85%) were identified as having delayed facial nerve paralysis. Those patients were clinically assessed and their medical records were reviewed. Tympanomastoid surgery included Cortical, modified radical, radical mastoidectomy and atticotomy. Results: There were only 3 cases of delayed facial palsy after tympanomastoid surgery (0.85%). Examination under microscope showed pus in mastoid cavities in two patients who developed facial palsy on day nine and day ten; while the third patient who developed facial palsy on day five had a clean mastoid cavity except the exposed facial nerve in horizontal segment. Appropriate management with antibiotics alongwith steroids in two patients having infection proved effective. While in third patient, the mastoid pack was removed and steroids alongwith prophylactic antibiotics were given resulting in recovery. Conclusion: The incidence of delayed facial nerve palsy (DFP) after Tympanomastoid surgery is low. The appropriate management & follow up is essential. The overall prognosis for delayed facial nerve palsy (DFP) in such cases is good.